1074. Management and Outcomes of Infective Endocarditis Due to Nutritionally Variant Streptococci. (26th November 2018) - Fida, Madiha; Mansoor, Tarab; Saleh, Omar Abu; Hamdi, Ahmed; Desimone, Daniel C; Wilson, Walter R; Steckelberg, James; Baddour, Larry M; Sohail, M Rizwan
Abstract: Background: Nutritionally variant streptococci (NVS) are an infrequent cause of infective endocarditis (IE) and management recommendations are based on weak levels of evidence largely derived from case reports, small case series, and animal models of experimental endocarditis. Moreover, taxonomic changes have led to some confusion in designation of these organisms. Methods: We retrospectively collected and analyzed data from 33 patients with NVS IE from 1970 to 2017. Only patients who met modified Duke Criteria for IE were included. Results: Mean patient age was 55 years and 61% were males. The most common comorbidities included diabetes mellitus (12%), malignancy (3%), heart failure (16%), coronary artery disease (25%), and chronic liver disease (9%). Predisposing valve abnormalities included rheumatic heart disease (11%), bicuspid aortic valve (22%), transplant valvulopathy (3%), mitral valve prolapse (3%), and congenital heart disease (11%). Cultures were reported as NVS (70%), Granulicatella species (18%) and Abiotrophia species (12%). Echocardiogram findings included vegetations (67%), new regurgitation (55%), perivalvular abscess (3%), mitral valve prolapse (3%), and ruptured mitral valve chordae (3%). Both prosthetic (26%) and native valve IE (74%) was seen, and the valves involved were aortic (37%), mitral (50%) and both aortic and mitral (13%). Complications were seen in 27% of patients, including heart failure (17%), splenic infarct (11%), stroke (8%), mycotic aneurysm (3%), and glomerulonephritis (2%). In vitro susceptibility to penicillin, ceftriaxone, and vancomycin was 88%, 80%, and 100%, respectively. The majority (77%) of patients were treated with a combination of β-lactam and aminoglycoside. Median duration of treatment was 33 days. Surgery was performed in 50% of patients with no significant difference in survival between those who were treated with combined medical/surgical treatment and those treated with medical therapy alone. Overall survival at 1, 4, and 10 years was 93%, 83%, and 66%, respectively. Conclusion: IE due to NVS is a rare entity and is associated with a high rate of serious complications and may involve multiple valves. Long-term, two-thirds of the patients survived more than 10 years. Disclosures: All authors: No reported disclosures.